Power reconfigurations and local government: affect and tension that reinvent the state - Lynch Cisneros, Jimena (2012)
Local state structure and local government (gestion) are shaped by spaces and personalities whose political and social relations generate unexpected effects. In this article, I explore this dynamic through an ethnography conducted with local municipal authorities at a swearing-in ceremony for the Urubamba Provincial Council (Junta) of Chicha Producers (Ajawasis) and a Carnaval Fiesta sponsored by the municipality. Specifically, the article analyzes how affects, histories, rumors and memories enter into tension with more formal or normative arenas of government, including established adminsitrative and legal processes. Seen from this perspective, the municipality ceases to appear as a static unit, to emerge instead as a fluid entity composed of very dynamic and shifting social processes and forces. Through an exploration of these processes, ethnography can help to open up the concept of gestion, to reveal how affect runs through the space of the municipality as through social life. The article offers a different entry into the study of the neoliberal State, by exploring how municipal authorities’ actions are shaped by relationships that go well beyond their official offices and hierarchies of the state.